"He Was Supposed to be With Me for the Rest of My Life": Meaning-Making in Bereaved Siblings' Online Stories. Issue 4 (1st October 2016) - Halliwell, Danielle; Franken, Noah
ABSTRACT: The present study applied relational dialectics theory to explore the competing discourses that animate bereaved siblings' online stories about their loss, as well as to understand how the interplay of these discourses constitutes meaning of sibling bereavement. Analysis of over 70 message board postings retrieved from online support groups revealed two main discursive struggles that characterize siblings' experiences of grief and loss: grieving as deviant behavior versus grieving as a normal process and the deceased as gone forever versus the deceased as still present . These findings illuminate the challenges bereaved siblings face as they attempt to mourn their deceased brother or sister and make sense of their grief within a societal context that oftentimes forgets or overlooks how traumatic it can be to lose a sibling.